Development of novel ferrocement light weight wall panels - Sivakumar, P.; Lakshmikandhan, K. N.; Ravichandran, R. (Journal of Structural Engineering, 2025)
The development of technologies has changed the growth of human lives which made the shortage of shelter. The natural and artificial disasters are the huge threat in the current scenario which needs to develop a structural system to serve the purpose. The advent of research made wider alternatives with many options to overcome these demands in terms of structurally light weight, stronger and cheaper, more ductile, durable and easy to construct / install. Innovative and cost effective methods are required to achieve affordable housing. Proper use of appropriate innovative technologies can enhance the quality of life, thereby enabling the community to move towards sustainable development. With the aim of developing affordable technologies and disseminating the appropriate and affordable technologies to the rural people, a study has been performed on developing a novel light weight and cost effective ferrocement wall panel. This technology reduces the usage of conventional building materials and it reduces the cost and the overall structural weight in turn. The objective of the study is to evolve a wall panel made of ferrocement with required stiffness and strength. Novel wall panels consisting of ferrocement skin and ribs were introduced to achieve the structural adequacy and constructability. Two types of ferrocement wall panels of size 1m × 1m were cast. One panel is cast with ribs around and the other panel is cast with reduced thickness and cross ribs. Nonlinear finite element analytical study was conducted on these panels. The results obtained from the experimental and analytical studies are presented and compared in this paper.